Shedding light on vitamin D: Unveiling the intricate links with lifestyle, demographics, and biochemical markers - Amr, Rula; Akash, Muhanad; Qatatsheh, Ala; Mayyas, Amal; Al-Qadiri, Hamzah; Akasheh, Rand (Acta Biomedica Atenei Parmensis, 2025)
Background: Vitamin D deficiency is a global public health issue, particularly prevalent in Arab countries due to limited sun exposure, cultural practices, obesity, and nutrient deficiencies. Research on its multifactorial determinants in Jordan remains limited. This study examines the demographic, biochemical, and anthropometric correlates of Vitamin D deficiency. Methods: A cross-sectional study was conducted among 385 participants aged 18–60 attending routine check-ups in Jordan. Data collection included structured questionnaires, anthropometric measurements, and biochemical analyses of serum 25-OHD, PTH, calcium, magnesium, and phosphorus. Multivariate logistic regression models incorporating interaction terms and subgroup-specific analyses identified predictors of Vitamin D deficiency. Model validity was assessed using calibration plots and the Area Under the Curve (AUC). Results: Vitamin D deficiency was observed in 58.96% of participants, disproportionately affecting females and low-income groups. Significant predictors included advancing age (OR = 1.05, 95% CI: 1.01–1.09, p = 0.012), income <850 J.D. (OR = 2.03, 95% CI: 1.14–3.60, p = 0.015), and heavy smoking (≥20 cigarettes/day; OR = 1.68, 95% CI: 1.03–2.75, p = 0.037). Elevated PTH levels and increased body fat percentage were significantly associated with deficiency (p < 0.001). Male smokers faced compounded risks (OR = 1.85, 95% CI: 1.12–3.04, p = 0.017). Conclusion: This study highlights the complex interplay of demographic, lifestyle, and biochemical factors in Vitamin D deficiency. Public health interventions targeting elevated PTH, adiposity, and socioeconomic barriers are essential to reducing deficiency and its risks.